The Edinburgh companion to literature and music - Sousa Correa, Delia da (Edinburgh : Edinburgh University Press, 2020)
This trailblazing companion charts and extends the work in this expanding interdisciplinary field and is an essential resource for researchers with an interest in literature and other media.
Literature and music in the nineteenth century. Introduction / Delia da Sousa Correa -- Music and the rise of narrative / Lawrence Kramer -- Opera. From English literature to Italian opera : a tangled web of translation / Denise P. Gallo ; James, Argento and The Aspern papers : "Orpheus and the Maenads" / Michael Halliwell ; Opera in nineteenth-century Italian fiction : reading "Senso" / Cormac Newark -- Nineteenth-century fiction and music. Stendhal at La scala : the birth of musical fandom / Gillen D'Arcy Wood ; George Eliot, Schubert and the cosmopolitan music of Daniel Deronda / Delia la Sousa Correa ; Music in Thomas Hardy's fiction : "You must not think me a hard-hearted rationalist" / John Hughes -- Music, poetry and song. Music in Romantic and Victorian poetry / Francis O'Gorman ; The princess and Tennyson's performance of childhood / Ewan Jones and Phyllis Weliver ; Tchaikovsky's songs : music as poetry / Philip Ross Bullock ; Wagner and French poetry from Nerval to Mallarmé : the power of opera unheard / Peter Dayan -- Literature and music in the twentieth and twenty-first centuries. Introduction / Stephen Benson -- Music and critical theory. Nelson Goodman : an analytic approach to music and literature studies / Eric Prieto ; Lyotard, phenomenology and the shared paternity of literature and music / Anthony Gritten -- Music and fiction since 1900. Music in Proust : the evolution of an idea / Mary Breatnach ; Music in Woolf's short fiction / Emma Sutton ; Listening in to D.H. Lawrence : music, body, feelings / Susan Reid ; E.M. Forster and music : listening for the amateur / Will May ; Beckett, music and the ineffable / Eric Prieto ; Jean Rhys and the politics of sound / Anna Snaith ; Music in contemporary fiction / Christin Hoene -- Music, poetry and song. Modernist poetry and music : Pound notes / Adrian Paterson ; Auden's imaginary song / T.F. Coombes ; Ivor Gurney : embracing and attacking A.E. Housman / Kate Kennedy ; Music and contemporary poetry : audience, apology and silence / Will May -- Opera. Le cas Debussy : layers of resonance from literature into music / Richard Langham Smith ; Britten, Austen and Mansfield Park / Will May ; Tippett, Eliot and Madame Sosostris / Oliver Soden -- Literature, pop music and sound. Worlds of sound in Louis MacNeice's early radio plays : "figure in the music" / Claire Davison ; "High fidelity, "added value" and the aesthetics of sound technology in literary modernism / Sam Halliday ; Words in popular songs / Dai Griffiths ; Notes on soundtracked fiction : the past as future / Justin St. Clair -- Coda. Origins and destinations : a future for literature and music / Michael L. Klein.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (ProQuest Ebook Central, viewed April 21, 2021).
JSTOR
Keywords: Music and literature; Literature -- History and criticism; Musique et littérature.; Littérature -- Histoire et critique; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Literature; Music and literature; Criticism, interpretation, etc